Functional Behaviour of Materials, Dielectric Materials
Este conjunto de animaciones introduce los principios de los materiales dielčtricos y los explica mediante la teora̕ de bandas. Contiene los siguientes elementos:The three main polarisation mechanisms on the microscopic scale Effect of inserting a dielectric material between two conducting plates Variation of frequency on the three polarisation mechanisms Resonances of the ionic and electronic polarization mechanisms Factors affecting dielectric constants: interactive game Effect of temperature on the dielectric constant Dielectric constant vs temperature in a polar material Dielectric breakdown: band theory